Adaptabilidade e estabilidade de híbridos de sorgo biomassa - Delgado, Ivan Dario (2017)
At present, there is a strong world demand for energy by increasing the population, that fact increase the consumption of the most varied products as is the case of electric energy. Sorghum bicolor (L.)Moench is an interesting raw material for the production of electric energy (cogeneration of energy) by burning in thermoelectric power plants. The objective of this work was to evaluate the interaction of genotypes by locations in biomass sorghum and to identify hybrids that associate high agronomic adaptability and stability. Thirty three experimental simple hybrids of biomass sorghum with sensitivity to photoperiod and three controls (BRS 655, Volumax and BRS 716) were evaluated in ten locations during 2014/2015 agricultural year. The experimental design was a 6 x 6 triple lattice with four grooves 5.0 m long, spaced 0.7 m apart, and only the two central lines has been considered as a useful area. The following characteristics were evaluated: flowering days (FLOW), plant height (PH), humidity (HUMID), yield of green mass (YGM) and yield dry mass (YDM). Individual and joint analyzes of variance were performed and the adaptability and stability of the hybrids to the locations were evaluated by the Toler (1990) and Annicchiarico (1992) methods.It was observed that the effects of genotypes, local and genotype interaction by sites (G x L) were highly significant (P <0.01), and the local effect contributed most to the phenotypic variation in most of the characters. The variation among the genotypes was expressive for all the characters. The interaction G x L was expressive in biomass sorghum mainly for the characters related to the production of biomass, having been predominantly complex. Experimental hybrids 1, 8, 22, 29, 31 and 33 and the BRS 716 commercial control stand out as the most promising because they presented high adaptability and agronomic stability according to the results obtained by the Toler and Annicchiarico methods.